KAJIAN PERBANDINGAN PRODUKTIVITAS DAN PENDAPATAN PERKEBUNAN POLA SISTEM INTEGRASI SAPI DAN KELAPA SAWIT (SISKA) DENGAN PERKEBUNAN TANPA POLA SISKA DI KABUPATEN SIAK - Susy Edwina; Jum'atri Yusri; Evi Maharani (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2019)
Oil palm plantation is a sector that significantly contributes to the economy of the people in Riau Province. Along with the development of oil palm industry, various technologies that aim to increase production and income of oil palm farmers have been introduced to the society. One of these technologies is Sistem Integrasi Sapi dan Kelapa Sawit (SISKA). The aim of SISKA is to increase the income of smallholder oil palm farmers. Farmers' income is expected to increase with business efficiency through the use of waste from livestock as fertilizer in oil palm plantations and new sources of income are emerging as a result of livestock business. This study aims to examine the comparison of productivity and income of plantation using SISKA and without using SISKA in Siak Regency. The study was conducted using a survey method in two representative locations, namely Sialang Palas Village, Lubuk Dalam District and Teluk Merbau Village, Dayun District. The research data are the primary data gathered by purposive sampling technique. The results showed that the productivity of plantations with SISKA that use organic fertilizer 18,899.93 kg/ha/year relatively higher than the productivity of plantations without SISKA that not use organic fertilizer 17,039.73/ha/year (significant at a 15%). The income of oil palm plantations using SISKA Rp 22,906,136.7/ha/year relatively higher than the income of the plantations without SISKA Rp 21,294,583.00/ha/year, however the difference is not statistically significant, because using SISKA increase the production cost.